The Diagnostic Value of Apparent Diffusion Coefficient and Proton Magnetic Resonance Spectroscopy in the Grading of Pediatric Gliomas. Issue 2 (March 2021) - Yao, Rong; Cheng, Ailan; Liu, Menglin; Zhang, Zhengwei; Jin, Biao; Yu, Hong
Abstract : Objective: The aims of this retrospective study were to assess the value of the quantitative analysis of apparent diffusion coefficient (ADC) and proton magnetic resonance spectroscopy ( 1 H-MRS) metabolites in differentiating grades of pediatric gliomas. Patients and Methods: Two hundred and nine pathology-confirmed pediatric gliomas (143 low-grade gliomas [LGGs] and 66 high-grade gliomas [HGGs]) were retrospectively analyzed on preoperative diffusion-weighted magnetic resonance imaging, of which 84 also underwent 1 H-MRS. The mean tumor ADC (ADCmean), minimum tumor ADC (ADCmin), tumor/normal brain ADC ratio (ADC ratio), and metabolites (choline/creatine ratio [Cho/Cr], N-acetylaspartate/creatine ratio [NAA/Cr], N-acetylaspartate/choline ratio [NAA/Cho], presence of lactate and lipid peaks) between LGGs and HGGs were analyzed. Results: There were significant negative correlations between the ADC values and glioma grade. Receiver operating characteristic analysis showed that the cutoff ADCmean value of 1.192 × 10 −3 mm 2 /s for the differentiation between low- and high-grade pediatric gliomas provided a sensitivity, specificity, accuracy, positive predictive value (PPV), and negative predictive value (NPV) of 77.6%, 80.3%, 78.5%, 89.5% and 62.4%, respectively; the cutoff ADCmin value of 0.973 × 10 −3 mm 2 /s resulted in a sensitivity, specificity, accuracy, PPV, and NPV of 86.0%, 90.9%, 87.6%, 95.3%, and 75.0%, respectively; the cutoff ADC ratio value of 1.384 resulted in a sensitivity, specificity, accuracy, PPV, and NPV of 73.4%, 87.9%, 78.0%, 92.9%, and 60.4%, respectively. A tendency for a positive correlation was found between Cho/Cr and glioma grade. A negative correlation was demonstrated between NAA/Cr or NAA/Cho and glioma grade. Statistical analysis demonstrated a threshold value of 2.601 for Cho/Cr to provide a sensitivity, specificity, accuracy, PPV, and NPV of 81.8%, 51.7%, 71.4%, 76.3%, and 60.0%, respectively, in dividing LGGs and HGGs; a threshold value of 0.705 for NAA/Cr to provide a sensitivity, specificity, accuracy, PPV, and NPV of 76.4%, 75.9%, 76.2%, 85.7%, and 62.9%, respectively; a threshold value of 0.349 for NAA/Cho to provide a sensitivity, specificity, accuracy, PPV, and NPV of 87.3%, 86.2%, 86.9%, 92.3%, and 78.1%, respectively. Conclusions: The ADC values and metabolites appeared to be significantly correlated to grade in pediatric gliomas. The predictive values may be helpful for preoperative diagnostic predictions.